Efficiency analysis of control algorithms in spatially distributed systems with chaotic behavior - Korus, Łukasz (Zielona Góra: Uniwersytet Zielonogórski)
The paper presents results of examination of control algorithms for the purpose of controlling chaos in spatially distributed systems like the coupled map lattice (CML). The mathematical definition of the CML, stability analysis as well as some basic results of numerical simulation exposing complex, spatiotemporal and chaotic behavior of the CML were already presented in another paper.
Keywords: controlling spatiotemporal chaos; coupled map lattice; system stability; Lyapunov exponents; net direction phase